Pendampingan Strategi Digital Marketing dalam Meningkatkan Penjualan Produk pada UMKM Spesial Bintang Aeng Baja Raja Bluto Sumenep - Rohmatullah, M. Akromi; Abrar, Unsul; Susantin, Nilli; Al Farisi, Salman; Susiyawati, Endang; Alif Qintari, Dina Aprilia; Fajriyah, Fani; Surur, Miftahus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
This community service activity aims to enhance the digital marketing capacity of the Spesial Bintang MSME in Aeng Baja Raja Village, Bluto Sub-district, Sumenep Regency. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The results of the activity show that the use of social media as part of a digital marketing strategy can increase business actors' knowledge of digital promotion, create consistent branding, and expand market reach. Implementation was carried out through mentoring and technical training, such as business account setup, content creation, and online interaction management. The final evaluation showed an increase in the MSME actors' understanding of digital marketing and a hope for continued assistance in the future. This program has proven effective in promoting sustainable marketing transformation for MSMEs and contributes to enhancing their competitiveness in the digital economy era.